2015
DOI: 10.4314/jasem.v19i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characterization and Pollution Index Determination of Leachates from Warri Waste Dumpsite, Southern Nigeria

Abstract: This study characterizes the leachates quality of an active dumpsite in Warri, Delta State and also analyses its contamination or pollution potential. Leachate Pollution Index (LPI) -a tool for quantifying pollution potential of leachates generated from dumpsites -has been used to quantify the leachates contamination potential of the dumpsite. The LPI values for the different sample locations L1, L2 and L3 were computed to be 5.69, 6.18 and 5.89 respectively with a mean value of 5.80, while the control had a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
13
1
1
Order By: Relevance
“…Leachate Pollution Index : LPI was calculated for Leachate from leachate collection tanks 1 and 2 of the sanitary landfill. The LPI values determined from 1 and 2 are compared with LPI standard for disposal proposed under Municipal Solid Waste (Management and Handling) Rules (2000) (Agbozu et al, 2015;Barjinder et al, 2014). The calculated LPI values L1 and L2 are 15.82 and 18.03 and the standard LPI value was 7.378.…”
Section: G Manjula Et Al: Analysis Of Solid Waste Dump Sitementioning
confidence: 99%
“…Leachate Pollution Index : LPI was calculated for Leachate from leachate collection tanks 1 and 2 of the sanitary landfill. The LPI values determined from 1 and 2 are compared with LPI standard for disposal proposed under Municipal Solid Waste (Management and Handling) Rules (2000) (Agbozu et al, 2015;Barjinder et al, 2014). The calculated LPI values L1 and L2 are 15.82 and 18.03 and the standard LPI value was 7.378.…”
Section: G Manjula Et Al: Analysis Of Solid Waste Dump Sitementioning
confidence: 99%
“…The LPI was expressed as shown in equation 1 [16,24]. 3content in the leachate was determined using the Stannous method [25].…”
Section: Fig 2 Two Un-engineered Dumpsites At Rumuosi and Igwurutamentioning
confidence: 99%
“…Many developed nations have been able to address the problem of leachate production in waste dumpsites through sanitary landfill systems, various wastes to wealth agenda and modern waste recycling and reuse technology [8, 9,10,11,12]. Many studies have been carried out on dumpsites in Nigeria [13,14,15,16,17,18,19] but these are dumpsite specific. Sackey and Meizah [20] revealed that waste dumpsites can be grouped into three distinctive grades by their ages (young, intermediate and old), which influence contamination levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este cenário é decorrente do aumento considerável da urbanização, do padrão de consumo e da mudança de hábitos alimentares, características evidenciadas, principalmente nos países em desenvolvimento. Neste cenário, torna-se cada vez mais necessária uma gestão de resíduos sólidos eficiente, demandando conhecimento e alternativas para que o destino final dos RSU seja ambientalmente correto, consequentemente reduzindo impactos ambientais (Agbozu et al, 2015;Khan et al, 2016) e a utilização de novas áreas (Wang et al, 2018), mitigando mudanças climáticas e reciclando recursos (Wang et al, 2020).…”
Section: Introductionunclassified